The Role of Photographer-Client Interpersonal Communication in Improving Working Relationships and Satisfaction in Creative Agency Photography Services - Kusnadi, Vigard Itnadia; Purworini, Dian (Jogjakarta Communication Conference (JCC), 2025)
This study aims to analyze the role of interpersonal communication, between photographers and clients in efforts to improve working relationships and satisfaction in creative agency photography services. Good and effective communication between the two parties is considered very important in creating a harmonious working relationship and leading to increased quality and work results and client satisfaction. Using the Social Exchange Theory (SET), this study will examine how the photography process, such as trust, fulfilment of client expectations and desires, and commitment to creative photography projects. Data were obtained through in-depth interviews. with creative agency photographers and clients who have worked together in creative agencies. The results of the study show that open and transparent communication can improve better and stronger working relationships, enrich client experiences, and increase satisfaction with the results of the photos obtained. This study provides an understanding and insight into the importance of interpersonal communication in the context of the creative industry and how communication can stimulate overall work results and client satisfaction.